Aggregate and cumulative chronic risk assessment for pyrethroids in the French adult population. (September 2020) - Vanacker, Marie; Quindroit, Paul; Angeli, Karine; Mandin, Corinne; Glorennec, Philippe; Brochot, Céline; Crépet, Amélie
Abstract: Pyrethroids are commonly used as insecticides in households, in agriculture or in veterinary and medicinal products. This study aimed to assess cumulative aggregate exposure to cyfluthrin, cypermethrin, deltamethrin and permethrin in adults in France and the associated health risk, and to identify major contributions of exposure sources and routes. External chronic exposures were estimated from dietary and several environmental sources for the oral, inhalation and dermal routes. Internal concentrations of five associated metabolites were simulated with a physiologically-based pharmacokinetic model. The predicted urinary concentrations were in same order of magnitude as those of the French ENNS biomonitoring survey. Dietary exposure, especially from cereals and animal products, was the major source of exposure. For the 1% of adults most highly exposed, dermal exposure to permethrin through medicinal and veterinary products was an important source of exposure. Considering alterations of motor, sensory and autonomic division, all individual margins of exposure were higher than 100, suggesting that no neurotoxic risk associated with the cumulative aggregate exposure to these four pyrethroids is expected for the French adult population. Highlights: Cumulative aggregate exposure to pyrethroids was estimated from multiple sources. Sources included diet, dust, inand outdoor air, veterinary and medicinal products. For more than 99% of the adult population, diet was the major source of exposure. For the 1% most exposed, veterinary and medicine products were important source. Risk of specific neurotoxic effects was nul in aggregating six exposure sources.